A Green Electrochemistry Experimental Kit: Student’s Achievements on Lectrofun 2.0 (Jurnal Pendidikan IPA Indonesia, 2021)
The study aimed at developing and evaluating a simple green electrochemistry experimental kit named Lectrofun 2.0. Lectrofun 2.0 is an educational kit equipped with a module built with the criteria of user-friendly, costeffective, and laboratory free. The basic concept of electrochemistry was introduced through a guided learning approach via the module. The objectives of this research were to (1) develop Lectrofun 2.0 module using green chemicals, recyclable and easily accessible materials and (2) evaluate the module effectiveness in terms of student achievement/understanding of the Electrochemistry topic. This is a Design and Development Research (DDR) using the ADDIE model as an instructional design model. The development phase involves the first objective of the study, while the evaluation phase involves the second objective. Total of 46 respondents of pre-post tests were involved in evaluating effectiveness of Lectrofun 2.0 in terms of student achievement/understanding of the topic. The findings showed that 73.9% of students from the treatment group showed 4-grade increment (from grade E to grade A). This study showed that Lectrofun 2.0 has a significant impact on enhancing learner comprehension of Electrochemistry topic, enjoyment in learning, and learning to care for the environment.